Effect of Ramadan fasting on intra ocular pressure changes in healthy subjects - Rahil Karimi Rad; Mohsen Nematy; Mohamad-Reza Sedaghat; Farshad Askarizade; Tahereh Rakhshandadi; Zahra Mahmoudi; Mehrane Mehramiz; Javad Heravian (Journal of Fasting and Health, 2017)
Introduction: Annually, millions of Muslims all over the world observe the fasting rules based on its measures; this highlights the importance of studies in this field as a worthwhile model for intermittent fasting. It is obvious that changes in lifestyle over fasting have outstanding effects on physiological parameters. The current study was carried out to investigate the IOP and serum electrolytes as two important factors that are influenced by human lifestyle. Methods: Eighty-nine fasting and healthy participants including men and women with mean age of 34.97 were included in our study based on the inclusion and exclusion parameters. During this project, Ramadan coincided with the summer (between June and July 2015). All participants were monitored by an expert examiner and blood samples were collected and IOP was measured by tonometer (Topcon, 1-75, Hasunuma-cho, Itabashi-KU, Tokyo, Japan 2014). The participants were examined one week before and one week after Ramadan. Results: There was a significant reduction in physiological IOP in healthy people after Ramadan. In line with this, the serum electrolytes were altered by fasting so that Na, K, Se experienced a significant decrease while serum phosphorous increased (P<0.05). Conclusion: Prolonged intermittent fasting in Ramadan changed IOP and serum electrolytes in healthy people within a normal range.